Evaluating the Causal Role of Gut Microbiota in Type 1 Diabetes and Its Possible Pathogenic Mechanisms - Zhou, He; Sun, Lin; Zhang, Siwen; Zhao, Xue; Gang, Xiaokun; Wang, Guixia (Frontiers in Endocrinology, 2020)
Type 1 diabetes (T1D) is a multifactorial autoimmune disease mediated by genetic, epigenetic and environmental factors. In recent years, the emergence of high-throughput sequencing has allowed us to investigate the role of gut microbiota in the development of T1D. Significant changes in the composition of gut microbiome, also termed dysbiosis, have been found in subjects with clinical or preclinical T1D, however, whether the dysbiosis is a cause or an effect of the disease remains unclear. Currently, increasing evidence have supported a causal link between intestine microflora and T1D development. In this review, we will focus on recent research regarding the associations between intestine microbiome and the T1D progression with an intention to evaluate the causality. We also discuss the possible mechanisms by which imbalanced gut microbiota lead to the of T1D.